Perceptive Study on Policy Interlinkage and Institutional Arrangement of Agrobiodiversity with Climate Change, Food And Nutrition - Khanal, S.; Joshi, B.K.; Shrestha, R.K.; Shivakoti, S.; Bhusal, A.; Shrestha, S. (Journal of Agriculture and Environment, 2022)
A study was conducted to find out interlink, assessing the implementation status, challenges and opportunities in mainstreaming the nexus of agro biodiversity, food and nutrition and climate change in policies and programs. An online survey tool (mwater) was used to deploy the pretested questionnaire to different professionals of Nepal. Out of 500 deployment, 54 responses were obtained. In most of the questions farmers were unable to decide the extent of interlink and implementation status, however, other professional groups perceived the linkage to be weak to moderate. Moreover, the implementation status of these policies were discerned to be less satisfactory. The opportunities and challenges are to be considered while plotting the action. For doing so, institutional setup for implementation and monitoring need to strengthen with wide consultation from policy formulation to implementation, impact assessment and review for having greater impacts on farming communities.